DSM-5 : handbook on the cultural formulation interview - Lewis-Fernández, Roberto; Aggarwal, Neil Krishan; Hinton, Ladson; Hinton, Devon E; Kirmayer, Laurence J (American Psychiatric Pub, 2015)
Clinicians will, of course, find the DSM-5® Handbook of the Cultural Formulation Interview indispensable, but administrators, policy makers, advocates, and other practitioners who work collaboratively to engage patients in the mental health care process will also value its clarity and comprehensiveness.